Duration of educated unemployment - Dody Setyadi; Yuli Sudarso; Muhammad Nahar; Sugiyanta Sugiyanta (Economic Journal of Emerging Markets, 2019)
The study aims to describe the characteristics of unemployed workers in Central Java Province and to determine the model of educated unemployment duration. It uses the linear regression model of 1721 workforces that are sampled from National Labor Survey 2015. The model regress the unemployment duration on age, sex, education level, income during unemployment period and GRDP of the industrial, service and agricultural sectors. Findings and Originality: The results show that variables of age, sex, the income of job seekers, education level at junior and senior high school level and GRDP in the agricultural sector have a positive effect on the unemployment duration. The variables of the status of household head, the high school education level, as well as the GRDP service sector, negatively effect the unemployment duration. Thus, it is recommended for the Central Java province government to develop service sectors to shorten the duration of unemployment in Central Java Province.Keywords: Unemployment Duration, Search Theory